1996
DOI: 10.1097/00005537-199611000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Concentration of Epinephrine for Vasoconstriction in Neck Surgery

Abstract: The addition of epinephrine to local anesthetics decreases bleeding, reduces systemic toxicity, and increases duration of action. However, epinephrine has significant side effects. Four concentrations of epinephrine were compared to determine the minimum concentration required for maximal vasoconstriction. Eighty-one subjects undergoing surgical procedures with general anesthesia were injected with 1% lidocaine containing varying concentrations of epinephrine. Blood flow measurements were then made at 1-minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 17 publications
0
57
0
2
Order By: Relevance
“…7 Phenylephrine, an α selective agonist, has also been largely abandoned in light of its unacceptable side effects including hypertensive crisis, cardiopulmonary compromise, pulmonary edema, and death. [9][10][11] As EES procedures have taken on greater complexity, the need for more powerful vasoconstriction has led to the emergence of topical concentrated (1:1000) epinephrine (CE) as a viable alternative to oxymetazoline. 10 As with cocaine and phenylephrine, complications arising from the administration of epinephrine have been reported including temporary hypotension, hypertensive crisis, tachycardia, cardiomyopathy, and cardiac arrhythmia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Phenylephrine, an α selective agonist, has also been largely abandoned in light of its unacceptable side effects including hypertensive crisis, cardiopulmonary compromise, pulmonary edema, and death. [9][10][11] As EES procedures have taken on greater complexity, the need for more powerful vasoconstriction has led to the emergence of topical concentrated (1:1000) epinephrine (CE) as a viable alternative to oxymetazoline. 10 As with cocaine and phenylephrine, complications arising from the administration of epinephrine have been reported including temporary hypotension, hypertensive crisis, tachycardia, cardiomyopathy, and cardiac arrhythmia.…”
mentioning
confidence: 99%
“…10,[12][13][14][15] Although these effects are of significant concern, they are largely the result of intravascular injection and there is limited literature on the safety of topical CE use or the optimal dose. 11,[16][17][18][19] One study concluded that topical CE use was safe in sinus surgery when combined with avoidance in patients with comorbid cardiac disease. 20 An additional practical concern with the use of CE arises from the potential for the masking of arterial bleeding, which may manifest postoperatively after the vasoconstriction has resolved.…”
mentioning
confidence: 99%
“…Hemostatis can be achieved by vasoconstriction. (11,12,13,14,15,16) Both topically applied and locally infiltrated vasoconstrictor agents reduces bleeding and improve visualization. (11)(12) Adrenaline is a commonly used vasoconstrictor agent, infiltrated locally reduce bleeding and improve visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine is the most commonly used constrictor of blood vessels and blood coagulation accelerator, especially on the skin or mucous membranes for bleeding control at the procedure site (Folwaczny et al, 1999;Koay and Orengo, 2002). It can reduce the absorption of local anesthetics into the bloodstream, resulting in decreased systemic toxic side effects, prolonged clinical duration of action and decreased surgical blood loss (Dunlevy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%